Relationship between type 2 diabetes mellitus and coronary artery lesion characteristics: a single center study - Dubey, Laxman; Guruprasad, Sogunuru; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2014)
Background: Coronary atherosclerotic burden is excessive in diabetic patients. The aim of present study was to assess the relationship between diabetes mellitus and plaque characteristics in patients with coronary artery disease.Methods: The coronary angiograms of 223 patients with significant obstructive lesions during April 2011 to May 2013 in College of Medical Sciences and Teaching Hospital were analyzed. The coronary lesions of patients with and without type 2 diabetes were compared. Results: 81 diabetic and 142 non-diabetic patients had significant coronary artery disease. Diabetic patients had more multivessel (64.2% versus 55.6%, p